Subgame consistent economic optimization an advanced cooperative dynamic game analysis - Yeung, David W.K (Static & Dynamic Game Theory: Foundations & Applications, 2012)
The prevalence of imperfect structures, externalities, and imperfect information in existing market systems prevents the market from serving as an efficient mechanism for resource allocation. In the presence of such failures, optimization of economic activities provides an effective remedial measure. Cooperative optimization suggests the possibility of socially optimal and individually rational solutions to decision problems involving strategic action over time; however, to guarantee that cooperation will last throughout the agreement period, the stringent condition of subgame consistency is required. This textbook presents a treatise on subgame consistent economic optimization, developing game-theoretic optimization techniques to establish the foundation for an effective policy menu to tackle sub-optimal circumstances that the conventional market mechanism fails to resolve. Topics covered include: * dynamic optimization; * group optimality and individual rationality; * time (optimal-trajectory-subgame) consistent economic optimization; * dynamic economic optimization under uncertainty and subgame consistency; * dynamically stable joint ventures; * collaborative environmental management; * discrete-time subgame consistent economic optimization.  This is the first book to thoroughly address the topic of subgame consistent economic optimization. It will be of particular interest as a research reference for game theorists, economists, mathematicians, policy makers, and corporate planners. With ample problems and exercises, it is also a useful text for graduate students in game theory.